2018
DOI: 10.1039/c8cc01753k
|View full text |Cite
|
Sign up to set email alerts
|

From fundamental supramolecular chemistry to self-assembled nanomaterials and medicines and back again – how Sam inspired SAMul

Abstract: This feature article provides a personal insight into the research from my group over the past 10 years. In particular, the article explains how, inspired in 2005 by meeting my now-husband, Sam, who had cystic fibrosis, and who in 2011 went on to have a double lung transplant, I took an active decision to follow a more applied approach to some of our research, attempting to use fundamental supramolecular chemistry to address problems of medical interest. In particular, our strategy uses self-assembly to fabric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 170 publications
(97 reference statements)
0
14
0
Order By: Relevance
“…2). 50 Each part of the building blocks plays a key role in both the self-assembling process and the subsequent heparin binding event. Even though the aliphatic tails are buried inside the micelles, their nature has a major influence on the micellar properties.…”
Section: Self-assembled Bindersmentioning
confidence: 99%
See 1 more Smart Citation
“…2). 50 Each part of the building blocks plays a key role in both the self-assembling process and the subsequent heparin binding event. Even though the aliphatic tails are buried inside the micelles, their nature has a major influence on the micellar properties.…”
Section: Self-assembled Bindersmentioning
confidence: 99%
“…At the interface of the two previous class of antidotes lies self-assembled binders, which yield nanoscale multivalent surfaces for heparin binding from the auto-aggregation of small cationic organic molecules. [50][51][52][53][54][55][56] Although this very promising (almost ideal?) approach provides highly efficient, degradable, inexpensive and easy-to-produce binders for heparin, further optimization is still needed to make these selfassembled structures stable enough to operate in highly competitive human blood, which is the ultimate target medium for clinical application.…”
Section: Take-home Messages On Heparin Neutralization and Monitoringmentioning
confidence: 99%
“…In order to obtain effective LMW hydro gelators, fine-tuning of the balance between the hydrophilic (soluble) and hydrophobic (insoluble) parts is essential. Examples of hydro gelators used for medical applications include derivatives of sugars such as DBS-COOH or DBS-CONHNH [2] used as a drug delivery system for naproxen (a non-steroidal anti-inflammatory drug) by pH mediated drug uptake and release [14,15]. Another class of hydro gelators is peptides of various composition and length, with aliphatic chains or aromatic groups.…”
Section: Hydro Gelatorsmentioning
confidence: 99%
“…Supramolecular chemistry includes and investigates highly ordered systems formed through intra- and intermolecular combination by weaker and reversible non-covalent interactions, and, also, it studies the recognition and selection of molecular components found in and for these structures [ 1 ]. Low molecular weight gelators (LMWGs) are a class of compounds with small dimensions (<3 kDa) [ 2 ] that present the property of self-association by physical interactions (hydrogen bonds, ionic, hydrophobic, van der Waals, π–π stacking) in a three-dimensional network, and have the ability to incorporate solvent molecules into their structure [ 3 ].…”
Section: Introductionmentioning
confidence: 99%